Using of Extracted Tannin from the Bark of Gray Avicennia Marina (Avicennia Marina) and Cordia Myxa (Cordia Myxa) Trees as Corrosion Green Inhibitors for Carbon Steel Alloy in Acidic Media. - AL-Tememi, Muhand K.; Hammood, Ahmed Y.; Al-Sawaad, Hadi Z (Iraqi Journal of Science, 2024)
This study evaluated the corrosion inhibiting properties of natural tannins extracted from gray Avicennia marina bark and Cordia myxa bark for carbon steel alloys. Such alloys are widely used in shipbuilding construction where corrosion poses challenges. Tannin extracts were tested as green inhibitors across varying concentrations in 0.5 M hydrochloric acid solution, a corrosive medium. Trials were conducted at different temperature parameters to determine the inhibition efficiencies. The amount of hydrogen gas released over time was quantified to compare corrosion rates in the absence and presence of tannin inhibitors. The Langmuir and Freundlich isotherm models for adsorption were also studied, as well as the kinetic and thermodynamic functions, where the change in free energy and activation energy were calculated. The results of the study showed a promising possibility to use the compounds under study as corrosion inhibitors for carbon steel with high efficiency up to more than 83% at a temperature of 25 degrees Celsius. The results showed an increase in the free energy change (ΔGcorro) values for the corrosion reaction in the presence of the inhibitors under study compared to corrosion in the absence of inhibitors, The free energy change (ΔGcorro) values at 25 degrees Celsius were (184.4538, 184.9246, 111.9616) kJ.mol-1 in the presence of the Avicennia marina inhibitor, Cordia myxa inhibitor and blank) consecutively. As a result, the speed of the corrosion reaction will decrease in the presence of inhibitors.